Spatial distribution of nicotine concentrations in Berlin’s surface waters and their potential sources - Markus Venohr; Christine Beusch; Tobias Goldhammer; Hanh Hong Nguyen; Simone Podschun; Claudia Schmalsch; Christian Wolter (Environmental Science and Pollution Research, 2025)
Nicotine is a ubiquitous emergent pollutant that primarily enters the environment through inappropriate disposal of cigarette butts. In a 7-week monitoring program, we collected 56 water samples from 14 lakes, 9 ponds, 9 rivers, 8 canals, and 2 canalized brooks in Berlin. Nicotine was detected in all investigated surface waters. Observed concentrations ranged between 7 ng/l and 1469 ng/l (mean 73 ng/l, median 28 ng/l). Rainy weather conditions generally led to an increase in nicotine concentrations, particularly in canals where concentrations were up to 16 times higher after rain events. For water bodies receiving sewer discharge, mean nicotine concentrations were positively related to population density, while concentrations in surface waters without sewer connections were more related to the presence of public transport stops or recreational areas. Our results highlight the high spatiotemporal variability of nicotine concentrations in urban surface waters. We recommend a temporary systematic daily or event-based monitoring of nicotine concentrations to support our findings and to better understand and quantify emission sources and concentration decay phases. This would improve our still incomplete knowledge about ecological impacts arising from long-term below-lethal nicotine concentrations in urban surface waters.